(untitled) (Human Factors in Design, 2024)
The evolution of sports fashion in its multiple modalities is constantly growing in both the design and technology areas, where new materials and finishes are developed to add value and quality to the final product. The objective of this research is to propose adaptations to the men’s sports shirts used by the Sesi Mogi das Cruzes paralympic goalball team. The target audience of this research are professional para-athletes, practitioners of sports activity, have some visual impairment and train every day. Informal interviews were carried out with para-athletes, health professionals and team coaches to understand what the main discomforts are caused by the current uniform. New uniforms were produced with the same modeling as the current uniform, but with a dry knit fabric, which aims to accelerate the speed of moisture transport from the body to the environment, keeping the shirt fabric dry. A field study was carried out with two volunteer para-athletes. On the first day para-athlete 1 wore the current uniform and para-athlete 2 the uniform proposed by this research and on the second day the para-athletes reversed the uniforms. To analyze the thermal comfort of the garments, photographs were taken with a thermographic camera, after the athletes had warmed up and after training with the ball. To analyze the other types of shirt comfort, interviews were conducted with the two para-athletes selected after warm-up and after training with the ball. The results showed that only replacing the knitted fabric with a dry knitted fabric was not enough to guarantee the thermal comfort of the proposed garment. To increase the comfort of the uniforms, it will be necessary to place a mesh fabric (small hole), to increase the ventilation of the clothing, in the regions where higher body temperature was detected. It was proposed the development of a prototype in seamless knitting, where there is the possibility of combining during the weaving of the piece areas of plain knit and areas with mesh.